2017
DOI: 10.5435/jaaos-d-16-00533
|View full text |Cite
|
Sign up to set email alerts
|

Factors Motivating Medical Students in Selecting a Career Specialty: Relevance for a Robust Orthopaedic Pipeline

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 29 publications
0
19
0
3
Order By: Relevance
“…This may have implications for recruitment of trainees into the field, especially given the weight that trainees place on quality of life . One study reported that quality of life is the second most important factor medical students consider when selecting a career specialty …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have implications for recruitment of trainees into the field, especially given the weight that trainees place on quality of life . One study reported that quality of life is the second most important factor medical students consider when selecting a career specialty …”
Section: Discussionmentioning
confidence: 99%
“…20 One study reported that quality of life is the second most important factor medical students consider when selecting a career specialty. 21 Additionally, interest groups and experiential opportunities have been associated with an increase in the yield of matches for other residencies and fellowships. 22 One study identified that implementation of a neurosurgical mentorship program, lectures, and creation of research opportunities demonstrated a 3.47-fold increase in match rates into neurosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…La vocación cumplida tiene un destino amplio, por lo que se denomina orientación profesional, dentro de la medicina quirúrgica o intervencionista, dentro de la formación recibida y la gratificación alcanzada con esta, según Rao y cols. 4 o lo que, a su vez, emprende las subespecialidades camino amplio con diversos senderos, con un capítulo previo común que hace al diagnóstico.…”
Section: La Vocación En Ortopedia Y Traumatologíaunclassified
“…3 Rao y cols. 4 consideran esta decisión como importante, compleja e individual con componentes inexplicables. Según Stabile, 5 la VOT busca identidades sólidas y autónomas, relacionando lo personal con lo institucional, así como un proyecto económico, con un laborioso destino final de acuerdo con Johnson.…”
unclassified
“…The so-called Generation Y can be identified by a strong willingness to perform, but also by the desire for autonomy and a well-adjusted work-life balance with a rising weight on leisure time [5]. The authorities of surgical societies have attempted to counteract this development with increased advertisement for surgical disciplines on both regional and nationwide levels [6].…”
Section: Review Introductionmentioning
confidence: 99%